Reduced protein C Global assay level in infertile women prior to IVF-ET treatment - Younis, Johnny S. (Springer US, 2013)
PURPOSE: In the last few years more robust evidence is emerging to point out at an increased rate of prematurity and low birth weight in singleton pregnancies following ART. Whether this increased rate is related to ART practice or to infertility per se, is still an open question. Our aim in this study was to explore this question by evaluating Protein C (ProC) Global assay in infertile women before ART treatment. METHODS: A cohort of 95 unselected and consecutive infertile women, eligible for ART, was prospectively recruited for the study. The control group included 77 matched healthy fertile women with a history of spontaneous conceptions. Pro C Global assay was evaluated in both groups. A full thrombophilic work-up was performed in the study group. RESULTS: ProC Global assay level was found to be significantly lower in the study as compared to the control group, corresponding to 0.78 ± 0.16 and 0.88 ± 0.16, respectively (P < 0.01). As well, abnormal ProC Global assay level of ≤ 0.8 was significantly higher in the study as compared to control group corresponding to 53 % and 29 %, respectively. ProC Global assay level was significantly lower in women within the study group found to have APCR, factor V Leiden and high factor VIII level, any thrombophilia or combined thrombophilia when compared to women without these thrombophilic risk factors. CONCLUSIONS: Reduced ProC Global assay level is encountered in infertile women prior to ART treatment. This finding may suggest a unique anticoagulation Protein C pathway in infertile as compared to fertile women. Further studies are encouraged to explore this finding.